Mountains - Hodge, Susie, 1960- ([S.l.] : Ticktock, 2008)
Examines the plant and animal life that live on some of the world's mountain regions and how they are able to survive.
Previously published: Great Britain : ticktock Media Ltd., 2007.
Includes bibliographical references (p. 31) and index.
5.7
3-6
Keywords: Mountain ecology